2012
DOI: 10.1007/978-1-61779-842-9_1
|View full text |Cite
|
Sign up to set email alerts
|

The Major Histocompatibility Complex: A Paradigm for Studies of the Human Genome

Abstract: The major histocompatibility complex (MHC) on chromosome 6 is one of the most intensively studied regions of the human genome and has many features which make it unique. It is the source of much research interest because of its role in autoimmune and infectious disease susceptibility, and of diagnostic interest because of its role in transplantation and rejection. It is the most gene-dense and SNP-rich region of the genome, with large number of complex haplotypes and other features which must be taken into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…To illustrate the difference between the two groups, a heatmap was generated using the 219 differentially expressed genes (Figure A). For the 134 upregulated genes, functional enrichment analysis revealed that they are most frequently associated with immune response, defense response, cellular response to cytokine stimulus, and antigen processing and presentation, which is consistent with previous discoveries (Figure B). , The major histocompatibility complex (MHC) regulates various kinds of immune reactions, including antigen presentation, cytotoxic response, and immune recognition . Notably, our analysis identified eight MHC class-II molecules overexpressed in MSI-H cancers, including CD74, HLA-DRA, HLA-DPB1, HLA-DPA1, HLA-DRB1, HLA-DQA1, HLA-DRB5, and HLA-DQB1 (Table ), suggesting that the efficient presentation of antigens to the helper arm of the immune system plays a major role in the immunogenicity of MSI-H cancers.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To illustrate the difference between the two groups, a heatmap was generated using the 219 differentially expressed genes (Figure A). For the 134 upregulated genes, functional enrichment analysis revealed that they are most frequently associated with immune response, defense response, cellular response to cytokine stimulus, and antigen processing and presentation, which is consistent with previous discoveries (Figure B). , The major histocompatibility complex (MHC) regulates various kinds of immune reactions, including antigen presentation, cytotoxic response, and immune recognition . Notably, our analysis identified eight MHC class-II molecules overexpressed in MSI-H cancers, including CD74, HLA-DRA, HLA-DPB1, HLA-DPA1, HLA-DRB1, HLA-DQA1, HLA-DRB5, and HLA-DQB1 (Table ), suggesting that the efficient presentation of antigens to the helper arm of the immune system plays a major role in the immunogenicity of MSI-H cancers.…”
Section: Resultssupporting
confidence: 90%
“…44,45 The major histocompatibility complex (MHC) regulates various kinds of immune reactions, including antigen presentation, cytotoxic response, and immune recognition. 46 Notably, our analysis identified eight MHC class-II molecules overexpressed in MSI-H cancers, including CD74, HLA-DRA, HLA-DPB1, HLA-DPA1, HLA-DRB1, HLA-DQA1, HLA-DRB5, and HLA-DQB1 (Table 1), suggesting that the efficient presentation of antigens to the helper arm of the immune system plays a major role in the immunogenicity of MSI-H cancers. Although not as dramatic as the upregulation of the MHC class II machinery, the MHC class I pathway seemed activated as well due to increased expression of HLA-F, TAP1, and TAP2 in MSI-H cancers (Table 1).…”
Section: Resultsmentioning
confidence: 82%
“…18 These SNPs are located mostly in the exon 2-3 region, and approximately one SNP is present every 20-30 nucleotides. 19 To date, few PCR-based methods for the specific detection of HLA-A or HLA-B alleles at the twofield classification have been published 20,21 and there have been no reports on the detection protocol of HLA-C alleles in general or the specific detection of the HLA-C*03:02 allele.…”
Section: Discussionmentioning
confidence: 99%
“…12S ribosomal takes part in cellular surface molecular translation and synthesis in the early stage of T cell activation [20][21][22]. MHC-III (hsc70t) is a participant in the cytotoxic cell activation process by coding complement C2, C3 and B factor [23,24]. gig18 (glutamic-oxaloacetic transaminase 1, GOT1) is an early marker of apoptosis in T cells [25,26].…”
Section: Discussionmentioning
confidence: 99%